Repair Work Ethnographies 2018
DOI: 10.1007/978-981-13-2110-8_3
|View full text |Cite
|
Sign up to set email alerts
|

‘A Good Enough Fix’: Repair and Maintenance in Librarians’ Digitization Practice

Abstract: The chapter examines how librarians deal with the unavoidable decay of archived and to-be-archived books in the context of a large-scale digitization project. The librarians' professional repair and maintenance work is specified by the complex nature of the books and the 'double bind' of their routine treatment. At the same time, they are to be preserved as jewels of cultural heritage and national identity and to be made available to interested visitors. The text focuses on the digitization process disclosing … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 26 publications
0
1
0
Order By: Relevance
“…Although previous studies of repair workers have demonstrated that diagnosis and repair are not separate, but rather intertwined practices (Orr 1996;Dant 2010;Houston 2019;Fürst 2019), they largely have focused on the process of searching for a particular cause. Categories used to group objects together as part of diagnosing a specific problem show that the repaired object is both a singular object and a representative of its type (Orr 1996;Fürst 2019). In this case, classification is not used to diagnose a specific problem, but rather to allocate resources and labor.…”
mentioning
confidence: 99%
“…Although previous studies of repair workers have demonstrated that diagnosis and repair are not separate, but rather intertwined practices (Orr 1996;Dant 2010;Houston 2019;Fürst 2019), they largely have focused on the process of searching for a particular cause. Categories used to group objects together as part of diagnosing a specific problem show that the repaired object is both a singular object and a representative of its type (Orr 1996;Fürst 2019). In this case, classification is not used to diagnose a specific problem, but rather to allocate resources and labor.…”
mentioning
confidence: 99%